Comment on “Islamic bioethics and modern globalization values: main points of contact” - Beresniovas, Romas (2024)
Commented Article: JAVADLI Gamar. Islamic bioethics and modern globalization values: main points of contact. Trans/Form/Ação: Unesp Journal of Philosophy, v. 47 n. 3, e0240087, 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/14681.